Digital Storytelling in Teaching Filipino Subject in Grade 7 Students - Abelon, Mona Liza G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study was conducted at San Guillermo National High School, San Marcelino, Zambales, Philippines. Its focus is on "DIGITAL STORYTELLING" IN TEACHING FILIPINO SUBJECT IN GRADE 7 STUDENTS. The study consisted of eighty-seven (87) participants who were divided into two groups or sections: the controlled group and experimental group. The researcher used an experimental design in the study because its purpose is to find out if “Digital Storytelling" influences the level of learning of students in the First Grading. The score obtained from the pretest and posttest were collected, tallied, and presented statistically using the mean, and MPs. The mean was used to find out the learning level of the controlled and experimental groups and to find out the significant differences of the mean scores in the pre-test and post-test of the two participating groups. In the pre-test and post-test conducted, it was recorded that the Controlled group Mean score is lower compared to Experimental group. Based on the collected results of the study, the following recommendations are made: a) DepEd is expected to allocate funds for trainings and workshops about Digital Storytelling so that Teachers have sufficient knowledge and boost the effectiveness of using this visual device; b) Teachers should prepare "Digital Storytelling" visual equipment for teaching literature in Filipino subject because it helps to cultivate students' performance; and c) This research needs to be continued so as to confirm the effectiveness of using 'Digital Storytelling' in teaching.